Capturing and Operationalizing Participation in Pediatric Re/Habilitation Research Using Artificial Intelligence: A Scoping Review - Kaelin, Vera C.; Valizadeh, Mina; Salgado, Zurisadai; Sim, Julia G.; Anaby, Dana; Boyd, Andrew D.; Parde, Natalie; Khetani, Mary A. (Frontiers in Rehabilitation Sciences, 2022)
Background: There is increased interest in using artificial intelligence (AI) to provide participation-focused pediatric re/habilitation. Existing reviews on the use of AI in participation-focused pediatric re/habilitation focus on interventions and do not screen articles based on their definition of participation. AI-based assessments may help reduce provider burden and can support operationalization of the construct under investigation. To extend knowledge of the landscape on AI use in participation-focused pediatric re/habilitation, a scoping review on AI-based participation-focused assessments is needed. Objective: To understand how the construct of participation is captured and operationalized in pediatric re/habilitation using AI. Methods: We conducted a scoping review of literature published in Pubmed, PsycInfo, ERIC, CINAHL, IEEE Xplore, ACM Digital Library, ProQuest Dissertation & Theses, ACL Anthology, AAAI Digital Library, and Google Scholar. Documents were screened by 2-3 independent researchers following a systematic procedure and using the following inclusion criteria: 1) focuses on capturing participation using AI; 2) includes data on children and/or youth with a congenital or acquired disability; and 3) published in English. Data from included studies were extracted (e.g., demographics, type(s) of AI used), summarized, and sorted into categories of participation related concepts. Results: 21 out of 3,406 documents were included. Included assessment approaches mainly captured participation through annotated observations (n=20; 95%), were administered in person (n=17; 81%), and applied machine learning (n=20; 95%) and computer vision (n=13; 62%). None integrated the child or youth perspective and only one included the caregiver perspective. All assessment approaches captured behavioral involvement, and none captured emotional or cognitive involvement or attendance. Additionally, 24% (n=5) of the assessment approaches captured participation-related constructs like activity competencies and 57% (n=12) captured aspects not included in contemporary frameworks of participation. Conclusions: Main gaps for future research include lack of: 1) research reporting on common demographic factors and including samples representing the population of children and youth with a congenital or acquired disability; 2) AI-based participation assessment approaches integrating the child or youth perspective; 3) remotely administered AI-based assessment approaches capturing both child or youth attendance and involvement; and 4) AI-based assessment approaches aligning with contemporary definitions of participation.